Maternity Leave and Paternity Leave: Evidence on the Economic Impact of Legislative Changes in High Income Countries - Serena Canaan; Anne Sophie Lassen; Philip Rosenbaum; Herdis Steingrimsdottir (Institute of Labor Economics (IZA), 2022)
Labor market policies for expecting and new mothers emerged at the turn of the nineteenth century. The main motivation for these policies was to ensure the health of mothers and their newborn children. With increased female labor market participation, the focus has gradually shifted to the effects that parental leave policies have on women\~Aâ'¬â"s labor market outcomes and gender equality. Proponents of extending parental leave rights for mothers in terms of duration, benefits, and job protection have argued that this will support mothers\~Aâ'¬Ëœ labor market attachment and allow them to take time off from work after childbirth and then safely return to their pre-birth job. Others have pointed out that extended maternity leave can work as a double-edged sword for mothers: If young women are likely to spend months, or even years, on leave, employers are likely to take that into consideration when hiring and promoting their employees. These policies may therefore end up adversely affecting women\~Aâ'¬â"s labor market outcomes. This has led to an increased focus on activating fathers to take parental leave, and in 2019, the European Parliament approved a directive requiring member states to ensure at least two months of earmarked paternity leave. The literature on parental leave has proliferated over the last couple of decades. The increased number of studies on the topic has brought forth some consistent findings. First, the introduction of short maternity leave is found to be beneficial for both maternal and child health and for mothers\~Aâ'¬â" labor market outcomes. Second, there appear to be negligible benefits from a leave extending beyond six months in terms of health out-comes and children\~Aâ'¬â"s long-run outcomes. Furthermore, longer leaves have little, or even adverse, influence on mothers\~Aâ'¬â" labor market outcomes. However, some evidence suggests that there may be underlying heterogeneous effects from extended leaves among different socioeconomic groups. The literature on the effect of earmarked paternity leave indicates that these policies prove effective in increasing fathers\~Aâ'¬â" leave-taking and involvement in childcare. However, the evidence on the influence of paternity leave on gender equality in the labor market remains scarce, and somewhat mixed. Finally, recent studies that focus on the effect of parental leave policies for a firm find that in general, firms are able to compensate for lost labor when their employees go on leave. However, if firms face constraints when replacing employees, it could negatively influence their performance.
Keywords: J08; J12; J13; J22; J23; 330; children; family; gender; parental leave; maternity leave; paternity leave; health; income; employment; parents; demography